The Effect of the QC (Quension Card) Assisted PBL (Problem Based Learning) Learning Model on the Learning Outcomes of Grade V Students of SDN 11 Singkawang - Zuhaira, Fitri; Rosmaiyadi, Rosmaiyadi; Wijaya, Andika Kusuma (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to 1) find out the difference in the science learning outcomes of fifth grade students in SDN 11 Singkawang before and after the used of the Problem Based Learning model assisted by Question Card; 2) find out the magnitude of the influence of learning outcomes of fifth grade students in SDN 11 Singkawang used Problem Based Learning assisted by Question Card. This study is a quantitative research with a one group pretest-posttest design. The sample used in this study was 22 students. The sampling technique used is the saturated sample technique. The results of the data analysis concluded that the prerequisite test used was a normality test used the shapiro wilk formula obtained by using a test, the data of this study was discontinuous normally with a P-value of 0.911 and a T-count of 0.913 for the pretest questions and a P-value of 0.911 and a T-count of 0.926 for the posttest questions. The results of the data analysis show that there is 1) a significant difference between the pretest and the posttest. This can be seen in the results of the paired t-test which shows that the t-count > t-table is 4.69 > 2.08. 2) the magnitude of the influence of learning outcomes with an effect size value of 3.73. Thus, the Problem Based Learning model assisted by Question Card has been proven to have an effect on student learning outcomes compared to the conventional model.